# Through the vertex of the parabola\[{{y}^{2}}=4x\]chords\[OP\]and\[OQ\]are drawn at

right angles to one another. The locus of middle point of\[PQ\]is

(a) \[{{y}^{2}}=x+8\]

(b) \[{{y}^{2}}=-2x+8\]

(c) \[{{y}^{2}}=2x-8\]

(d) \[{{y}^{2}}=x-8\]

Last updated date: 19th Mar 2023

•

Total views: 307.5k

•

Views today: 2.86k

Answer

Verified

307.5k+ views

Hint: To find the locus of the middle point of two points on the parabola, write the points in parametric form and then find the middle point of the points. Use the fact that the product of slope of any two perpendicular lines is\[-1\].

We have the parabola\[{{y}^{2}}=4x\]. We want to find the locus of middle point of two

points on the parabola such that the chords joining two points of the parabola to its vertex are

perpendicular to each other.

We know that the vertex of parabola of the form\[{{y}^{2}}=4ax\]is\[\left( 0,0 \right)\].

Thus, we have\[\left( 0,0 \right)\]as the vertex of the parabola\[{{y}^{2}}=4x\].

To find the locus of middle point of\[PQ\], let’s write the points in parametric form.

We know that any point of the parabola\[{{y}^{2}}=4ax\] is of the form\[\left( a{{t}^{2}},2at \right)\].

Substituting\[a=1\]in the above equation, we have the two points on our parabola as\[P\left(

{{t}_{1}} \right)=\left( t_{1}^{2},2{{t}_{1}} \right)\]and\[Q\left( {{t}_{2}} \right)=\left(

t_{2}^{2},2{{t}_{2}} \right)\].

We know that the equation of any line passing through origin is of the form\[y=mx\].

Let’s assume that the equation of line joining origin and\[P\left( {{t}_{1}} \right)=\left(

t_{1}^{2},2{{t}_{1}} \right)\]is of the form\[y={{m}_{1}}x\].

Substituting the point\[P\left( {{t}_{1}} \right)=\left( t_{1}^{2},2{{t}_{1}} \right)\]in the equation of

line, we have\[2{{t}_{1}}={{m}_{1}}t_{1}^{2}\].

Thus, we have\[{{m}_{1}}=\dfrac{2}{{{t}_{1}}}\]. \[...\left( 1 \right)\]

Let’s assume that the equation of line joining origin and\[Q\left( {{t}_{2}} \right)=\left(

t_{2}^{2},2{{t}_{2}} \right)\]is of the form\[y={{m}_{2}}x\].

Substituting the point\[Q\left( {{t}_{2}} \right)=\left( t_{2}^{2},2{{t}_{2}} \right)\]in the equation of

line, we have\[2{{t}_{2}}={{m}_{2}}t_{2}^{2}\].

Thus, we have\[{{m}_{2}}=\dfrac{2}{{{t}_{2}}}\]. \[...\left( 2 \right)\]

We know that the two chords passing through\[P\]and\[Q\]are perpendicular, so the product of

their slope is\[-1\].

Using equation\[\left( 1 \right)\]and\[\left( 2 \right)\], we have\[{{m}_{1}}{{m}_{2}}=-1\].

\[\begin{align}

& \Rightarrow \dfrac{2}{{{t}_{1}}}\times \dfrac{2}{{{t}_{2}}}=-1 \\

& \Rightarrow {{t}_{1}}{{t}_{2}}=-4 \\

\end{align}\]

Thus, we can write\[{{t}_{1}}\]as\[{{t}_{1}}=\dfrac{-4}{{{t}_{2}}}\]. \[...\left( 3 \right)\]

We know that the middle point of two points of the form\[\left( {{x}_{1}},{{y}_{1}} \right)\]and\[\left(

{{x}_{2}},{{y}_{2}} \right)\]is\[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\].

Substituting\[{{x}_{1}}=t_{1}^{2},{{y}_{1}}=2{{t}_{1}},{{x}_{2}}=t_{2}^{2},{{y}_{2}}=2{{t}_{2}}\]in the

above equation, we have\[\left( \dfrac{t_{1}^{2}+t_{2}^{2}}{2},\dfrac{2{{t}_{1}}+2{{t}_{2}}}{2}

\right)\]as the mid point of the points\[P\left( {{t}_{1}} \right)\]and\[Q\left( {{t}_{2}} \right)\].

Let’s assume\[x=\dfrac{t_{1}^{2}+t_{2}^{2}}{2},y=\dfrac{2{{t}_{1}}+2{{t}_{2}}}{2}\].

Substituting equation\[\left( 3 \right)\]in the above equation, we have\[x=\dfrac{{{\left( \dfrac{-

4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2},y=\dfrac{2\left( \dfrac{-4}{{{t}_{2}}} \right)+2{{t}_{2}}}{2}\].

Solving the above equation, we get\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}}

\right)}^{2}}+t_{2}^{2}}{2}\]and\[y=\dfrac{-4}{{{t}_{2}}}+{{t}_{2}}\].

Squaring the second equation, we get\[{{y}^{2}}={{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}-

8\].

\[\Rightarrow {{y}^{2}}+8={{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}\]

Substituting the above equation in\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2}\],

we get\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2}=\dfrac{{{y}^{2}}+8}{2}\].

\[\Rightarrow 2x={{y}^{2}}+8\]

Hence, the correct answer is\[{{y}^{2}}=2x-8\].

Note: It’s necessary to use the fact that the two chords are perpendicular and hence, the product of their slope is\[-1\].

We have the parabola\[{{y}^{2}}=4x\]. We want to find the locus of middle point of two

points on the parabola such that the chords joining two points of the parabola to its vertex are

perpendicular to each other.

We know that the vertex of parabola of the form\[{{y}^{2}}=4ax\]is\[\left( 0,0 \right)\].

Thus, we have\[\left( 0,0 \right)\]as the vertex of the parabola\[{{y}^{2}}=4x\].

To find the locus of middle point of\[PQ\], let’s write the points in parametric form.

We know that any point of the parabola\[{{y}^{2}}=4ax\] is of the form\[\left( a{{t}^{2}},2at \right)\].

Substituting\[a=1\]in the above equation, we have the two points on our parabola as\[P\left(

{{t}_{1}} \right)=\left( t_{1}^{2},2{{t}_{1}} \right)\]and\[Q\left( {{t}_{2}} \right)=\left(

t_{2}^{2},2{{t}_{2}} \right)\].

We know that the equation of any line passing through origin is of the form\[y=mx\].

Let’s assume that the equation of line joining origin and\[P\left( {{t}_{1}} \right)=\left(

t_{1}^{2},2{{t}_{1}} \right)\]is of the form\[y={{m}_{1}}x\].

Substituting the point\[P\left( {{t}_{1}} \right)=\left( t_{1}^{2},2{{t}_{1}} \right)\]in the equation of

line, we have\[2{{t}_{1}}={{m}_{1}}t_{1}^{2}\].

Thus, we have\[{{m}_{1}}=\dfrac{2}{{{t}_{1}}}\]. \[...\left( 1 \right)\]

Let’s assume that the equation of line joining origin and\[Q\left( {{t}_{2}} \right)=\left(

t_{2}^{2},2{{t}_{2}} \right)\]is of the form\[y={{m}_{2}}x\].

Substituting the point\[Q\left( {{t}_{2}} \right)=\left( t_{2}^{2},2{{t}_{2}} \right)\]in the equation of

line, we have\[2{{t}_{2}}={{m}_{2}}t_{2}^{2}\].

Thus, we have\[{{m}_{2}}=\dfrac{2}{{{t}_{2}}}\]. \[...\left( 2 \right)\]

We know that the two chords passing through\[P\]and\[Q\]are perpendicular, so the product of

their slope is\[-1\].

Using equation\[\left( 1 \right)\]and\[\left( 2 \right)\], we have\[{{m}_{1}}{{m}_{2}}=-1\].

\[\begin{align}

& \Rightarrow \dfrac{2}{{{t}_{1}}}\times \dfrac{2}{{{t}_{2}}}=-1 \\

& \Rightarrow {{t}_{1}}{{t}_{2}}=-4 \\

\end{align}\]

Thus, we can write\[{{t}_{1}}\]as\[{{t}_{1}}=\dfrac{-4}{{{t}_{2}}}\]. \[...\left( 3 \right)\]

We know that the middle point of two points of the form\[\left( {{x}_{1}},{{y}_{1}} \right)\]and\[\left(

{{x}_{2}},{{y}_{2}} \right)\]is\[\left( \dfrac{{{x}_{1}}+{{x}_{2}}}{2},\dfrac{{{y}_{1}}+{{y}_{2}}}{2} \right)\].

Substituting\[{{x}_{1}}=t_{1}^{2},{{y}_{1}}=2{{t}_{1}},{{x}_{2}}=t_{2}^{2},{{y}_{2}}=2{{t}_{2}}\]in the

above equation, we have\[\left( \dfrac{t_{1}^{2}+t_{2}^{2}}{2},\dfrac{2{{t}_{1}}+2{{t}_{2}}}{2}

\right)\]as the mid point of the points\[P\left( {{t}_{1}} \right)\]and\[Q\left( {{t}_{2}} \right)\].

Let’s assume\[x=\dfrac{t_{1}^{2}+t_{2}^{2}}{2},y=\dfrac{2{{t}_{1}}+2{{t}_{2}}}{2}\].

Substituting equation\[\left( 3 \right)\]in the above equation, we have\[x=\dfrac{{{\left( \dfrac{-

4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2},y=\dfrac{2\left( \dfrac{-4}{{{t}_{2}}} \right)+2{{t}_{2}}}{2}\].

Solving the above equation, we get\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}}

\right)}^{2}}+t_{2}^{2}}{2}\]and\[y=\dfrac{-4}{{{t}_{2}}}+{{t}_{2}}\].

Squaring the second equation, we get\[{{y}^{2}}={{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}-

8\].

\[\Rightarrow {{y}^{2}}+8={{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}\]

Substituting the above equation in\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2}\],

we get\[x=\dfrac{{{\left( \dfrac{-4}{{{t}_{2}}} \right)}^{2}}+t_{2}^{2}}{2}=\dfrac{{{y}^{2}}+8}{2}\].

\[\Rightarrow 2x={{y}^{2}}+8\]

Hence, the correct answer is\[{{y}^{2}}=2x-8\].

Note: It’s necessary to use the fact that the two chords are perpendicular and hence, the product of their slope is\[-1\].

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Name the Largest and the Smallest Cell in the Human Body ?

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

A ball impinges directly on a similar ball at rest class 11 physics CBSE

Lysosomes are known as suicidal bags of cell why class 11 biology CBSE

Two balls are dropped from different heights at different class 11 physics CBSE

A 30 solution of H2O2 is marketed as 100 volume hydrogen class 11 chemistry JEE_Main

A sample of an ideal gas is expanded from 1dm3 to 3dm3 class 11 chemistry CBSE